Acid rain decelerates the decomposition of Cunninghamia lanceolata needle and Cinnamomum camphora leaf litters in a karst region in China. Issue 1 (30th January 2019) - Tang, Li; Lin, Yonghui; He, Xingbing; Han, Guomin
Abstract: Acid rain is generally believed to inhibit litter decomposition, but this inhibition effect often depends on local soil environmental factors such as nutrient and physicochemical property. Karst ecosystem is typically characterized by rich CaCO3, which can potentially react with H + from acid rain. However, it is unknown whether the effect of acid rain on litter decomposition will be mitigated by this potential reaction. To investigate the effect of acid rain on decomposition, we undertook a field experiment on the decomposition of litters of Cunninghamia lanceolata needle and Cinnamomum camphora leaf during 1 year in a karst region in subtropical China. Contrary to hypothesis, litter decomposition was significantly decelerated by acid rain for the two litter types. For C. lanceolata litter, at the end of incubation, we noted that moderate acid rain resulted in the highest loss in mass (43%), while severe one showed the lowest loss (39%); for C. camphora litter, the mass loss was as follows: ambient treatment (66%) > moderate treatment (56%) > severe treatment (42%). Also microbial activities (including CO2 flux, fungal biomass and microbial degrading enzymes) showed similar variation patterns among acid rain treatments to mass loss. These responses indicated that the deceleration effect of acid rain on litter decomposition did not depend on calcareous soil as well as litter quality. Together, these results suggest that acid rain had a predominant controlling of litter decomposition over soil and litter qualities, and this information may be useful for predicting functional responses of karst ecosystem to environmental factors. Abstract : The litter decomposition was significantly decelerated by acid rain for Cunninghamia lanceolata needle and Cinnamomum camphora leaf. Also microbial activities (including CO2 flux, fungal biomass and microbial degrading enzymes) showed similar variation patterns among acid rain treatments to mass loss. These responses indicated that the deceleration effect of acid rain on litter decomposition did not depend on calcareous soil as well as litter quality.